Analisis Nilai Karakter Permainan Tradisional Pada Buku Siswa Kelas 4 SD Kurikulum 2013 - Aisah, Nur (Social, Humanities, and Educational Studies (SHES): Conference Series, 2020)
The purpose of this study was to determine the character values contained in traditional games in the 4th grade elementary school curriculum 2013. This study used a qualitative descriptive study with a phenomenological approach. This study describes events or phenomena with data in the form of words. Methods of data collection using observation and documentation. The data validity technique uses source triangulation. The data analysis technique uses data collection, data selection, conclusion drawing, and validation. The results showed that 13 traditional games in the 4th Grade Elementary School Student Book published by the Ministry of Education and Culture were gobak sodor, forts, engklek, kasti, marbles, tug of war, woodpeckers and insects, fish, frogs and lizards, hunters and the Javan rhinoceros. , build punden terraces, gangsing, enggrang, and sepak takraw containing values of honest character, tolerance, discipline, hard work, creative, independent, democratic, respecting achievement, friendly/communicative, peace loving, social care, and responsibility.